Executives’ fringe benefits in Langkawi hotels - Ahmad, Rozila (Universiti Utara Malaysia Press, 2013)
An important element of human resources, compensation is an effective tool to attract and retain skilled employees.Despite its crucial importance the literature concerning executive compensation in the hotel industry is very few especially those focusing on fringe benefits.To fill the gap in the hotel human resources literature, this study assessed the level of fringe benefits provided to executives in the hotel industry. The purpose of this empirical study was to gain information regarding executives’ compensation in the industry.Stratified random sampling technique was used to ensure that the findings represented hotels of various star-ratings.A total of 250 questionnaires were distributed to the ratio of 6:3:4 to three-, four- and five-star hotels and 104 were returned. The findings revealed that there is a statistically significant difference in the fringe benefits given between three -, four - and five-star hotels, and the star rating of hotels positively correlates with the level of fringe benefits provided to hotel executives.